Metacognição como estratégia pedagógica para o ensino coletivo de instrumentos de sopro da família dos metais no âmbito de um curso de licenciatura em música - Serafim, Leandro Libardi (2021)
Although several studies have emphasized the importance of metacognition in musical learning and development, only a small number have examined its use in the collective and heterogeneous teaching of musical instruments in undergraduate music education programs, particularly with respect to wind instruments of the brass family. Therefore, within the framework of an interpretive/constructivist paradigm, the goal of this qualitative research study of an exploratory nature was to describe the use of metacognitive strategies in the processes of teaching and learning these instruments and reading music notation, during the course Complementary Instrument - Winds 1, in an undergraduate program in music education at a public university in northeastern Brazil. A 32-hour pedagogical intervention was carried out employing didactic materials and pedagogical approaches designed in the interest of promoting, in addition to learning these instruments and reading music notation, the metacognitive development of the students. The sample was comprised of eight students (n = 8), four females and four males, aged 19-22 years old. Data collection tools included a Questionnaire on Sociodemographic Data and Prior Musical Knowledge, nine Reflection Reports, a Reflection Questionnaire and a Music Study and Performance Practice Test. A content analysis was conducted using coding strategies based on the work of Garcia and Dubé (2012) and Whitebread et al. (2009). A total of 856 metacognitive indices were identified that allowed the researcher to describe the characteristics of the learning process, highlighting aspects related to metacognitive knowledge about people, tasks and strategies, as well as the management of mental processes related to planning, control and regulation. The results of this research study suggest that metacognition can be an important tool in the contexts of collective teaching of musical instruments, allowing not only for learning and/or musical development, but also for the development of pedagogical skills